2019
DOI: 10.1111/bjet.12769
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the roles of school leaders and teachers in a school‐wide adoption of flipped classroom: School dynamics and institutional cultures

Abstract: While numerous studies have explored the efficiency of instructional design supported by ICT (eg, Blanc, 2018) and the effectiveness of ICT-integrated learning environments (eg, Sun, Lin, Wu, Zhou, & Luo, 2018), most of them are focused on designed instructional activities, procedures or learning environments. How ICT supports instructional reforms in natural settings, especially on an institutional level, still needs further exploration. AbstractWhile the development of digital technologies provides genero… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(31 citation statements)
references
References 45 publications
0
24
0
1
Order By: Relevance
“…The 10 articles in this final competency category presented competencies uncovered during implementing or transitioning to BT. While most of the articles focused on the skills that individual teachers need, Bingham ( 2016 ) and Sun and Gao ( 2019 ) reported the importance of clear roles for teachers, administrators, and other leaders in establishing school-wide BT. Competencies for individual teachers focused on overcoming barriers related to implementing BT.…”
Section: Resultsmentioning
confidence: 99%
“…The 10 articles in this final competency category presented competencies uncovered during implementing or transitioning to BT. While most of the articles focused on the skills that individual teachers need, Bingham ( 2016 ) and Sun and Gao ( 2019 ) reported the importance of clear roles for teachers, administrators, and other leaders in establishing school-wide BT. Competencies for individual teachers focused on overcoming barriers related to implementing BT.…”
Section: Resultsmentioning
confidence: 99%
“…The study of management reported by Sun and Gao () is more ethnographic. It describes a large‐scale intervention that focusses on technology adoption as experienced across the whole school community.…”
Section: The Meso‐layermentioning
confidence: 99%
“…An ecological perspective involves awareness of the rich variety of settings within which educational practice takes place: accordingly, research will need to confront this variety, to capture and express it. For example, from the corpus of research reported in this Special Issue, there is clearly a significant gulf between “a Chinese middle‐high boarding school” (Sun & Gao, ) and a primary school in a culturally diverse area of New Zealand (Davis et al , ). Yet we should retain faith in the central place of the findings from such case studies.…”
Section: Moving Forwardmentioning
confidence: 99%
“…Since innovation develops over time (Yunus, 2018) education has no exemption. Technology-integrated education is one of the chosen ways as it offers unlimited resources to education (Sun & Gao, 2019). It is also a medium of delivering and receiving information between teacher and students (Zaki & Yunus, 2015).…”
Section: Introductionmentioning
confidence: 99%